Salivary Immune Parameters as A Predictor of Oral Diseases - Aljubouri, Esraa A.; Alaubydi, Mouruj. A.; Alsaadi, Yahya D. (Iraqi Journal of Science, 2023)
Diabetes mellitus (DM) is a metabolic and hormonal disorder in which the body does not produce sufficient or respond ordinarily to insulin, leading to an increase in blood sugar (glucose) levels. This disordered has many side effects on body health, one of them being oral health. This study aimed to find these effects on several oral immune parameters included (IL6, CRP, and alpha-amylase) and the possible use of these parameters in the prediction of oral health and further risk sequel. A total of 91 specimens including 51 DM patients and 40 apparently healthy individuals were enrolled in this study which was carried out from November/2021 to February/2022. The results revealed that, abnormal increase of both IL6 and CRP in the saliva of both experimental groups, with no significant differences between them. Simultaneously, alpha-amylase shows significant increases in the saliva of the patient’s group than in the control. Receiver operating characteristic (ROC) analysis with Area under the curve (AUC) confirmed that alpha-amylase can be used as a predictor parameter reflected oral and body health.